Attaining the 2030 Sustainable Development Goal of Responsible Consumption and Production - Naomi Birdthistle; Rob Hales (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. Attaining the 2030 Sustainable Development Goal of Responsible Consumption and Production focuses on Sustainable Development Goal number twelve (SDG#12): escaping the trap of excessive output and overconsumption. Examining family businesses in Germany, Ireland, and the United Kingdom, each case study presents a unique perspective from their respective country, analysing how SDG#12 reconsiders the unsustainable patterns of consumption and production that threaten both human and planetary wellbeing. The case studies presented generate insights and key takeaways into the role of family businesses in sustaining the livelihoods of current and future generations. The United Nations (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 that would help engender an improved, fairer, and more sustainable world – one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editors Naomi Birdthistle and Rob Hales bring together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia – such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations, and philanthropic centres – this book series appeals equally to those with a general interest in entrepreneurship and business.
Keywords: 330; SDG 12; Process Definition; Business Strategy; Sustainability; Circular Economy; Environmental Management Systems; United Nations